Semiextending Nailing for Combined Shaft and Ankle Injuries of the Leg. (August 2016) - Probe, Robert
Abstract : Summary: Over recent years, orthopaedic traumatologists have been gaining experience with tibial nailing in the extended position. Originally developed to address the complexities of alignment in proximal tibial fractures, this technique has also proven valuable in the treatment of tibial shaft fractures combined with ankle injuries. Depicted in this video presentation is the surgical techniques used to simultaneously address a spiral fracture of the distal tibia associated with a large coronal plane fracture of the tibial articular surface. Discussed are leg positioning, technical aspects of the medial approach, strategies for preliminary ankle stabilization, and fine details of aligning the tibial component of the injury. With a growing body of evidence suggesting similar knee outcomes with semiextended and conventional infrapatellar approaches, it is anticipated that this technique will become increasingly popular in coming years.